Presacral, Retrorectal Dermoid Cyst in a Female Patient - Case Report - Karagjozov, Aleksandar; Antovikj, Svetozar; Milev, Ilija; Kadri, Edjevit (My University, 2012)
The retrorectal tumors are well defined, classified and understood pathological entities in the literature but in practice they represent very unusual and infrequent pathology. We are presenting a case from the group of dermoid congenital retrorectal cysts which at first manifested itself clinically as inflamatous retrorectal cyst that had spontaneously rupture in the postanal space with local (tumor, dolor, calor, rubor, function laesa and fluctuation) and systemic signs of infection (fever, rise temperature, leukocytosis). On physical examination there was typical postanal dimple which gives a picture of “double anus” on inspection. On DRE there was retrorectal soft tumor with compression of the anorectum. Diagnosis was confirmed with MRI and fistulography. After a palliative treatment for abscending cyst with incision, Penrose drainage and daily washings with antiseptic solutions the patient was transferred in specialized institution - the Clinic of Digestive surgery at the Medical Faculty in Skopje for definitive treatment. The operation was performed with the patient in jack-knife position with conventional preparing of the colon and prophylactic antibiotic regiment started preoperatively. An on table anoscopy was performed at first which sowed typical mammilla at the internal opening of the fistulous communication of the cyst with the rectum about 3 cm above the posterior crypt of Morgagni. We started with excision of the external opening, and preceded with whole excision of the pericystic granulomatous tissue about 14 cm in length till the presacral point. The fistulous communication was excised completely and the rectum was sutured in two layers with separate sutures. The wound was laid open and the patient was discharged on the 5-th postoperative day. About one month the wound was treated with daily washings with antiseptic solutions and after that one month with only water. After two mounts the defecation is normal, the wound is sealed and there are no signs of inflammation and secretion locally. The retrorectal tumors are difficult for treatment as well as for diagnosis where even punctional biopsy is not recommended so they should be treated in specialized institutions by experienced surgeons from the moment of diagnosis to the definitive surgical treatment.
Keywords: retrorectal cyst; excision; fistulous communication